Worldliness and Respect for Nature: an Ecological Appreciation of Hannah Arendt's Conception of Culture. (1st February 1998) - Whiteside, K.H.
Abstract : Arendt's conception of culture could supersede claims that nature's intrinsic value or human interests best ground environmental ethics. Fusing ancient Greek notions of non-instrumental value and Roman concerns for cultivating and preserving worldly surroundings, culture supplies an ethic for the treatment of nonhuman things. Unlike a system of philosophical propositions, an Arendtian ecology could only arise in public deliberation, since culture's qualitative judgements are intrinsically linked to processes of political persuasion.